2017
DOI: 10.14453/aabfj.v11i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Uncertainty as a Contingent Factor of Business Strategy Choice Decision: Introducing an Alternative Measurement of Uncertainty

Abstract: This study aims to examine a contingent factor of business strategy decisions, namely environmental uncertainty. The study applies secondary data as an alternative method to analyze technological uncertainty: a component of environmental uncertainty. To examine environmental uncertainty, this study develops an Environmental Uncertainty Index (EUI). Utilizing a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period from 2009 to 2012 and a multinomial logistic regression, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 30 publications
3
42
0
2
Order By: Relevance
“…Some scholars have conceived uncertainty as the objective dimension of the external environment, while others have viewed uncertainty as the interpretation of the perceptual process that helps decision-makers in conceptualizing the environment (Milliken 1987a, b). Arieftiara et al (2017), Duncan (1972), and Lawrence and Lorsch (1967) presented some important measures of uncertainty, which the present study builds upon. Lawrence and Lorsch (1967) identified the uncertainty variables associated with departments, such as research, manufacturing, and marketing, and assessed the degree of uncertainty within the three different organization subsystems.…”
Section: Review Of the Literaturementioning
confidence: 98%
See 4 more Smart Citations
“…Some scholars have conceived uncertainty as the objective dimension of the external environment, while others have viewed uncertainty as the interpretation of the perceptual process that helps decision-makers in conceptualizing the environment (Milliken 1987a, b). Arieftiara et al (2017), Duncan (1972), and Lawrence and Lorsch (1967) presented some important measures of uncertainty, which the present study builds upon. Lawrence and Lorsch (1967) identified the uncertainty variables associated with departments, such as research, manufacturing, and marketing, and assessed the degree of uncertainty within the three different organization subsystems.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…Extant studies have found that organizational design is often influenced by the uncertainties that prevail in the business environment (Latan et al 2018;Lawrence and Lorsch 1967). Past studies (e.g., Arieftiara et al 2017;Dill 1958;Duncan 1972;Lawrence and Lorsch 1967;Singh 2020) have attempted to gauge the "objective", as well as, the "perceived" environmental uncertainty, and to examine the relationship between these "objective" and perceptual measures. Attempts to measure the "effect" of such environmental uncertainty on the strategy formation within an organization is not so frequent, with Venkataramanaiah and Kumar's (2011) and Arieftiara et al (2017) review papers presenting contemporary reviews on the subject.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations